Local Culture-Based Ethnomathematics for Strengthening STEAM Literacy in Transdisciplinary Mathematics Education - Nur Ismiyati; St. Zulaiha Nurhajarurahmah (Darul Yasin Al Sys, 2026)
This study aims to describe the implementation of local culture-based ethnomathematics in strengthening STEAM literacy within transdisciplinary mathematics learning. A qualitative descriptive approach was employed through thematic analysis of 14 student projects developed by postgraduate students in the Mathematics Education Program at Universitas Negeri Makassar during the 2025/2026 academic year. Data were collected through document analysis of student project reports focusing on local culture, geometry, arts, digital technology, and STEAM-based learning. Data analysis was conducted through coding, categorization, theme synthesis, and interpretation. The findings reveal that local culture provides an effective context for STEAM-based transdisciplinary learning by connecting mathematical, scientific, artistic, and technological concepts with students’ real-life experiences. The project themes were predominantly related to local Sulawesi cultural elements, including Tongkonan traditional houses, Lipa’ Sabbe motifs, traditional weaving, Sayyang Pattudu, and natural patterns based on symmetry and fractals. STEAM integration was reflected in the use of GeoGebra and Canva for concept visualization, digital design, and mathematical exploration. The transdisciplinary projects also supported the development of numeracy, scientific, digital, visual, and cultural literacy, as well as 21st-century skills. The study concludes that integrating local culture, transdisciplinary learning, and digital technology has strong potential as an innovative mathematics learning model for supporting the implementation of the Merdeka Curriculum. These findings contribute to mathematics education by demonstrating how ethnomathematics can strengthen STEAM literacy while preserving local cultural values in technology-enhanced learning environments.